DEVELOPMENT OF AN INTERCTIVE MEDIA APPLICATION GUIDE TO PLANTING HYDROPONIC VEGETABLES AS AN EFFORTS TO EMPOWER PEJAMBON VILLAGE FARMERS GROUP - Anantyo, Sandy (Institut Bakti Nusantara, 2023)
Hydroponic farming has emerged as an innovative solution to enhance agricultural productivity and environmental sustainability. This research aims to introduce an interactive media application as a guide for cultivating hydroponic vegetables, with a focus on empowering farmer groups in the village of Pejambon. The research methodology involves an initial survey phase to assess the level of knowledge and needs of the farmer groups, followed by direct observation of their farming practices. The development of the application incorporates information technology and communication, featuring step-by-step guides, video tutorials, and discussion forums. The application is designed to provide in-depth information on the selection of plant types, hydroponic techniques, and the management of nutrients. The research outcomes are expected to improve the practical knowledge and skills of the farmer groups in implementing hydroponic methods while facilitating information exchange among group members. Consequently, the development of this interactive media application is anticipated to serve as an effective empowerment tool, supporting increased crop yields and the well-being of the farmer groups in the village of Pejambon. In conclusion, the implementation of this application is expected to be a positive step in promoting sustainable agriculture and empowering local farmer groups in the region. The development of an interactive media application for hydroponic vegetable cultivation using the MDLC (Multimedia Development Life Cycle) method has had a positive impact on empowering the farming community in Pejambon Village. The stages of analysis in aligning the application with user needs to ensure that the content is suitable for their knowledge and skills. The intuitive interface and diverse multimedia elements in the design phase aim to enhance understanding and make the learning experience more engaging.